The Effect of Partnership Loans, Books and Types of Business on the Productivity of MSME Partnership Partner PT. Perkebunan Nusantara III Medan - Ine Sitompul, Elwina; Febriyanti Tarigan, Fransiska; Silsila Tabrani, Bilqis; Faisal Mirza, Deni (Journal Research of Social Science, Economics, and Management, 2022)
This research is one of the things that must be done by final semester students to obtain a bachelor of management degree. Human resource management must be owned by every agency or company in which it is a group of people who have the ability in each unit that has been placed. This study examines micro, small and medium entrepreneurs which is to analyze and test whether there is an effect of partnership loans, bookkeeping and type of business on productivity. The population of this study are entrepreneurs who are under the fostered partners of PT. Perkebunan Nusantara III Medan and sampling was carried out using the slovin formula. To obtain data, data collection carried out by researchers was by distributing questionnaires to respondents as many as the number of research samples which were then processed by the SPSS application with multiple linear regression test, normality test and hypothesis testing with the standard error used was 0.05 (5% ). The results of this study indicate that there is a positive and significant effect between partnership loans, bookkeeping and type of business on productivity. The magnitude of the effect of partnership loans, bookkeeping and type of business on productivity can be seen through the determination test, which is 25%.